1996
DOI: 10.1039/cc9960001287
|View full text |Cite
|
Sign up to set email alerts
|

DNA hydrolysis by stable metal complexes

Abstract: Stable cobalt(rI1) complexes promote hydrolysis of the DNA phosphodiester backbone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…À6 s À1 for 1 mM C o at 37 C and pH 7.5] of CoCyc toward the supercoiled pUC18 measured in this study is comparable to the reported value (k o =1Â10 À5 s À1 for 1 mM C o at 37 C and pH 7.6) 6 for that toward supercoiled pUC9. When the supercoiled DNA was incubated with the Cyc-containing resins without Co(III) ion, cleavage of the DNA was negligible under the conditions of the kinetic measurements.…”
Section: à14supporting
confidence: 78%
See 1 more Smart Citation
“…À6 s À1 for 1 mM C o at 37 C and pH 7.5] of CoCyc toward the supercoiled pUC18 measured in this study is comparable to the reported value (k o =1Â10 À5 s À1 for 1 mM C o at 37 C and pH 7.6) 6 for that toward supercoiled pUC9. When the supercoiled DNA was incubated with the Cyc-containing resins without Co(III) ion, cleavage of the DNA was negligible under the conditions of the kinetic measurements.…”
Section: à14supporting
confidence: 78%
“…A mechanism (2) has been proposed 6 for the catalytic action of the Co(III) complexes: the Co(III) center binds the phosphate anion of the phosphodiester linkage and the adjacent Co(III)-bound hydroxide ion makes intramolecular attack at the phosphorus atom of the bound substrate.…”
Section: à14mentioning
confidence: 99%
“…These studies are also important to understand the toxicity of metal based drugs [7]. Cobalt complexes have gained importance for their applicability in the biological field [8][9][10]. Some of the previous reports show that hexamine cobalt complexes induce DNA condensation [11,12] and can be used as RNA hairpins probe [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…
The literature suggests that only stable, tetra-coordinated metal complexes are capable of cleaving phosphodiester bonds [12]. We, therefore, decided to synthesize various stable Zn II complexes, as they are known to play an important role in phosphodiester cleavage [13], and to study their DNA-cleavage abilities.
…”
mentioning
confidence: 99%